Penyelesaian Sengketa Waris Adat Minangkabau Dalam Pendekatan Hukum Waris Indonesia - Martinus Ahmad; ADI NUR ROHMAN; SUGENG (Faculty of Law Universitas Bhayangkara Jakarta Raya, 2026)
The settlement of Minangkabau customary inheritance disputes within Indonesia’s legal practice reveals an encounter and persistent tension between communal, matrilineal customary law and the national positive law system, which is individualistic, formal, and procedural in nature. Minangkabau customary law places pusaka tinggi (ancestral property) as collective property of the clan managed by the mamak kepala waris, whereas national inheritance law, both under the Civil Code and the Compilation of Islamic Law, conceives inheritance as individual rights that may be transferred and proven juridically. These differing paradigms frequently generate conflict when customary inheritance disputes are brought before state courts. This research examines two main issues: (1) how inheritance disputes are resolved under Minangkabau customary law and Indonesian positive law; and (2) how the regulation of Minangkabau customary inheritance dispute resolution is positioned within the framework of Indonesian positive law. The study employs a normative juridical method with statutory and case approaches, focusing on the analysis of Supreme Court Decision No. 2480 K/Pdt/2010, Supreme Court Decision No. 11 K/Pdt/2013, and Pariaman District Court Decision No. 77/Pdt.G/2024/PN Pmn. The findings indicate that courts consistently prioritize formal aspects, particularly legal standing and evidentiary standards, so that the applicability of customary law depends heavily on the parties’ ability to translate customary structures into the framework of civil procedural law. Although customary law is normatively recognized, its operationalization remains subordinative. This study recommends reconstructing civil procedural law to be more accommodative of the collective and dynamic characteristics of Minangkabau customary law, thereby fostering a more equitable harmonization between national legal certainty and customary justice